2019
DOI: 10.3390/ijms20030594
|View full text |Cite
|
Sign up to set email alerts
|

The TSPO Ligands 2-Cl-MGV-1, MGV-1, and PK11195 Differentially Suppress the Inflammatory Response of BV-2 Microglial Cell to LPS

Abstract: The 18 kDa Translocator Protein (TSPO) is a marker for microglial activation as its expression is enhanced in activated microglia during neuroinflammation. TSPO ligands can attenuate neuroinflammation and neurotoxicity. In the present study, we examined the efficacy of new TSPO ligands designed by our laboratory, MGV-1 and 2-Cl-MGV-1, in mitigating an in vitro neuroinflammatory process compared to the classic TSPO ligand, PK 11195. We exposed BV-2 microglial cells to lipopolysaccharide (LPS) for 24 h to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 61 publications
3
37
0
1
Order By: Relevance
“…Additionally, the authors concluded that the neuroprotective effect of Emapunil might be associated with the partial alteration of neurosteroid levels, which can counteract neuroinflammatory responses [65]. Together with other studies applying TSPO ligands for the treatment of brain damage, this investigation showed promising results about exploiting TSPO as a possible therapeutic target for α-synucleinopathies [28,66]. However, greater efforts must be made to fully disclose the influence of TSPO ligands on dopaminergic degeneration.…”
Section: Tspo and Parkinson Disease (Pd)mentioning
confidence: 79%
“…Additionally, the authors concluded that the neuroprotective effect of Emapunil might be associated with the partial alteration of neurosteroid levels, which can counteract neuroinflammatory responses [65]. Together with other studies applying TSPO ligands for the treatment of brain damage, this investigation showed promising results about exploiting TSPO as a possible therapeutic target for α-synucleinopathies [28,66]. However, greater efforts must be made to fully disclose the influence of TSPO ligands on dopaminergic degeneration.…”
Section: Tspo and Parkinson Disease (Pd)mentioning
confidence: 79%
“…TSPO has low affinity for these ligands (both approximately 825 nM) due to the elongation of the alkyl side chains, which reduces their lethal effects as compared to the classical TSPO ligands as described previously (21,22). The anti-inflammatory effects of MGV-1 and 2-Cl-MGV-1 were described previously (23).…”
Section: Methodsmentioning
confidence: 89%
“…Initially, two concentrations of the ligands were used based on preliminary studies, 1 and 25 μM final concentrations. Eventually, the chosen final concentration of the ligands in the current study was 25 μM, as used previously (22,23). Following incubation, the cells were exposed to CS for 30 and 60 min in order to optimize the cell death assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was performed to reveal to what extent glycine affected the viability, activation state and secretory activity of microglial cells during inflammation. BV-2 cells were stressed with a combination of LPS and IFN-γ over 24 h. LPS is the most common pro-inflammatory stimulus and causes inflammatory reactions in primary microglia and BV-2 cells [17,18], and IFN-γ is released during CNS injury [18][19][20]. Approximately 90% of the genes induced in BV-2 cells after LPS exposure were also found in primary microglia and showed similar reaction patterns [21], which warrants this cell line as a suitable experimental model.…”
Section: Discussionmentioning
confidence: 99%